The con men: hustling in New York City - Williams, Terry M. (Studies in transgression, 2015)
Alibi : portrait of a con man -- City cons and hustles -- The con crew -- The con game as street theater -- Petty street hustles -- Canal street as venus flytrap -- The numbers game -- New York tenant hustles -- A drug hustle : the crack game -- NYPD and the finest cons -- Wall Street cons